Re-imagining Africanisation of sustainable epistemologies and pedagogies in (South) African higher education: A conceptual intervention - Sebola, M.; Mogoboya, M.J. (South African Journal of Higher Education, 2020)
This article aims to foreground the conceptual premise that (South) African academia should be the hub of Afrocentric knowledge production, both at theoretical and practical levels, through the efficacy of both “academic” and “non-academic” intellectuals. We further argue that these intellectuals, undergirded by epistemic desires for organic knowledge production, should be considered germane in the process of Africanising (South) African academia. The Afrocentricity theory, Antonio Gramsci’s (1971) and Syed Hussein Alatas’ (1977) conceptualisation of intellectuals serve as lynchpins for the conceptual forte of this article.